The Potential of Ketungau and Silat Shales in Ketungau and Melawi Basins, West Kalimantan: For Oil Shale and Shale Gas Exploration - Santy, Lauti Dwita; Panggabean, Hermes (Geological Agency, 2013)
DOI:Â 10.17014/ijog.v8i1.154The Ketungau and Melawi Basins, in West Kalimantan, are Tertiary intramontane basins of which the potential for economic conventional oil and gas discoveries have not previously been confirmed. The Ketungau Basin is bordered by the Melawi Basin in the south. Besides non-ideal trapping mechanisms, another major problem in these basins is source rock maturation. Nevertheless, both basins are promising to be explored for oil shale and shale gas energy resources. Therefore, the aim of this paper is to give some perspectives on their source rocks, as an input for the evaluation of the potential of unconventional oil and gas. About twenty samples collected from the Ketungau and Melawi Basins were analyzed using pyrolysis and organic petrographic methods. The results show a poor to good quality of source rock potential. The Ketungau shale, which is the main source rock in the Ketungau Basin, is dominated by type III, immature, and gas prone kerogen. The Silat shale, which is the main source rock in the Melawi Basin, is dominated by type II, immature to early mature, mixed gas, and oil prone kerogen. In the field, Ketungau and Silat Formations have a widespread distribution, and are typically 900 m to 1000 m thick. Both the Ketungau and Silat shales occur within synclinal structures, which have a poor trapping mechanism for conventional oil or gas targets, but are suitable for oil shale and shale gas exploration. This early stage of research clearly shows good potential for the future development of unconventional energy within the Ketungau and Melawi Basins.